Mitochondrial genome characterization and mitogenome phylogenetics in the central Mexican Stenopelmatus talpa complex (Orthoptera: Stenopelmatidae: Stenopelmatini) - Paola Xanath Ruiz-Mendoza; Jovana M. Jasso-Martínez; Jorge Gutiérrez-Rodríguez; Ernesto Samacá-Sáenz; Alejandro Zaldívar-Riverón (Revista Mexicana de Biodiversidad)
The Stenopelmatus talpa species-group (Stenopelmatidae) comprises cricket-like orthopterans distributed across the Trans-Mexican Volcanic Belt (TMVB) morphotectonic province and adjacent areas in central Mexico. Despite recent efforts, the taxonomy and evolutionary relationships for members of this complex still are far from completely known. Here we generated and characterized the mitochondrial (mt) genome of 14 specimens of the S. talpa species-group and evaluated its species limits with the cox1 barcoding locus. Moreover, based on the mt genome DNA sequence data, we also reconstructed its phylogenetic relationships and made inferences about its biogeographic history based on a relaxed molecular clock analysis. A total of 9 species were delimited using a 2% pairwise distance criterion, which were consistent with our best estimate of phylogeny. The relationships recovered for the S. talpa species-group were similar although with more recent divergence time estimates than those obtained in a previous phylogenetic study, suggesting that its origin and subsequent diversification in the TMVB followed an east-central pattern, with its earliest divergence occurring during the late Pliocene to early Pleistocene.